ASSESSMENT AND INFLUENCE OF A FAMILY PHYSICIAN ON THE HEALTH STATUS OF THE POPULATION OF AMALGAMATED TERRITORIAL COMMUNITIES - V. I. Potseluiev (Eastern Ukrainian Medical Journal, 2020)
Introduction. Primary health care is the most important part of the health system. Family physicians, as representatives of this link, are key figures who are assigned a number of responsibilities for the prevention, diagnosis, and treatment of both adults and children. An indicator of the effectiveness of their work is the level of satisfaction of citizens with the quality of service. To understand the effectiveness of reform implementation, the authors evaluated the activities of the family physician and its influence on the health of citizens living on the entrusted territory.The aim of the study is an empirical analysis of the selection criteria, frequency and reasons for the citizens' visits to a family physician in the amalgamated territorial communities of the Sumy region.Materials and methods. During the research, methods of a systematic approach and comparative analysis were used. The study was conducted in the form of a survey. Calculations and processing of statistical information were carried out using the "OSA" application.Study results and discussion. The paper shows the condition of primary care as a result of the health system reform. The sociological survey on the work of family physicians in the amalgamated territorial communities concerned the criteria for choosing a family physician, the frequency of requests for medical care, and the reasons for requests, in particular for preventive purposes. The analysis showed that the percentage of signing declarations is relatively high. However, a certain formality of this process was observed, since a significant percentage of citizens who signed the declaration have never met their family physician. The result indicates that citizens often do not seek medical care in outpatient clinics on the territory of the amalgamated territorial community, and they rarely visit the physician for preventive purposes. According to respondents, the reason for not seeking prevention is the lack of need.Conclusion. A high percentage of residents of the amalgamated territorial communities signed declarations with family physicians. However, having analyzed the survey data, we can note a rather formal attitude to this procedure, since many residents seek medical services in other medical institutions. It is a consequence of the insufficient effectiveness of the reform of primary health care and insufficient attention on the part of local authorities to provide outpatient clinics with qualified specialists. There is a need to raise awareness about the importance of preventive measures.